PEMANFAATAN MEDIA ANIMASI VIDEO DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI 21 TANJUNG JABUNG TIMUR - Oktafiana, Devi; Anwar, Khoirul; Saputra, Edi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning achievement through the use of animated video media in Islamic Religious Education for seventh-grade students at SMP Negeri 21 Tanjung Jabung Timur. The research employed Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection. Data were collected through learning achievement tests, observations, and documentation, and were analyzed using a quantitative descriptive approach. The findings indicate that the use of animated video media effectively improved students’ learning outcomes, with the mastery level increasing from 50% in Cycle I to 82% in Cycle II, thereby exceeding the Minimum Mastery Criteria (MMC) set at 75. In addition, the animated video media enhanced students’ attention and motivation during the learning process. These results are expected to serve as a reference for teachers and educational institutions in developing innovative learning strategies aligned with the demands of 21st-century education.